ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP PADA MATERI POLA BILANGAN - Nur Amaliatunnisa; Nita Hidayati (IKIP Siliwangi, 2023)
The purpose of this study was to determine the problem-solving abilities of junior high school students in solving mathematical problems in number pattern material. This research was conducted in one of the public schools located in Karawang Regency. There are 4 indicators of problem solving, namely, the adequacy of known and requested information data, problem solving strategies, completion of mathematical models and arguments, and re-examination of the solutions obtained. This research was conducted with a subject of 17 class VIII students with a qualitative descriptive method. The technique used in data collection was using the descriptive test method, while the technique used to analyze the data was using the average percentage. Meanwhile, the percentage of indicators (1) the stage of identifying data is 27.06%; (2) the problem solving strategy stage, amounting to 21.17%; (3) skill stage in solving mathematical models 9.41%; (4) the concluding stage of 8.23%. The results of the data analysis show that most of the mathematical problem solving abilities of junior high school students are still low.